2018
DOI: 10.1186/s10033-018-0283-9
|View full text |Cite
|
Sign up to set email alerts
|

Car Fuel Economy Simulation Forecast Method Based on CVT Efficiencies Measured from Bench Test

Abstract: Researchers face difficulties in studying the effects of driveline efficiency on car fuel economy via bench and road tests because of long working periods, high costs, and heavy workloads. To simplify the study process and shorten test cycles, a car fuel economy simulation forecast method for combining computer simulation forecasting with bench tests is proposed. Taking a continuously variable transmission (CVT) as the research object, a transmission efficiency model based on a bench test is constructed. An op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…When the speed ratio changes, however, there are additional losses due to increased sliding. The CVT losses have been taken into account through the model proposed in [24].…”
Section: The Cvt Bev Simulation Modelmentioning
confidence: 99%
“…When the speed ratio changes, however, there are additional losses due to increased sliding. The CVT losses have been taken into account through the model proposed in [24].…”
Section: The Cvt Bev Simulation Modelmentioning
confidence: 99%
“…The offset for the universal joint is the angle between the front and rear angles, whereas the offset for the driveshaft is the angle between the differential and wheels. Literature shows the significance of the speed in determination the transmission system efficiency [153] in comparison to the role of other factors. It has been shown that the maximum efficiency of the transmission systems is not higher than 95% [144,153].…”
Section: Loss and Efficiency In The Single And Multi-speed Transmission Systemsmentioning
confidence: 99%
“…Literature shows the significance of the speed in determination the transmission system efficiency [153] in comparison to the role of other factors. It has been shown that the maximum efficiency of the transmission systems is not higher than 95% [144,153]. Thus, this portion of the loss must not be ignored when the total efficiency of an EV is studied.…”
Section: Loss and Efficiency In The Single And Multi-speed Transmission Systemsmentioning
confidence: 99%
“…Controlling the slip rate within an appropriate range is expected to improve the transmission efficiency of the metal belt, but only from an engineering perspective [14]. Lei et al [15] conducted a CVT transmission efficiency model base on bench test in which gasoline with low fuel consumption by measured, however, they ignored the influence of slip. The friction coefficient is expressed as a function of the ratio of the moving arc to the wrap angle of the pulley.…”
Section: Figure 2 Failure Of Metal Belt and Metal Sheetmentioning
confidence: 99%